Sisters and the English Household Domesticity and Women's Autonomy in Nineteenth-Century English Literature - Wallace, Anne D. (Anthem Press, 2018)
Sisters and the English Household revalues unmarried adult sisters in nineteenthcentury English literature as positive figures of legal and economic autonomy representing productive labor in the domestic space. As a crucial site of contested values, the adult unmarried sister carries the discursive weight of sustained public debates about ideals of domesticity in nineteenth-century England. Engaging scholarly histories of the family, and providing a detailed account of the 70-year Marriage with a Deceased Wife's Sister controversy, Anne Wallace traces an alternative domesticity anchored by adult sibling relations through Dorothy Wordsworth's journals; William Wordsworth's poetry; Mary Lamb's essay "On Needle-Work"; and novels by Jane Austen, Elizabeth Gaskell, Charles Dickens, Dinah Mulock Craik and George Eliot. Recognizing adult sibling relationships, and the figure of the adult unmarried sibling in the household, as primary and generative rather than contingent and dependent, and recognizing material economy and law as fundamental sources of sibling identity, Sisters and the English Household resets the conditions for literary critical discussions of sibling relations in nineteenth-century England.